2016
DOI: 10.5539/enrr.v6n3p146
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Distribution, Enrichment, and Potential Toxicity of Trace Metals in the Surface Sediments of Okinawa Mangrove, Southwest Japan

Abstract: Surface sediments along the coast of Okinawa Island were analyzed to determine their geochemical compositions, and to assess sediment quality and the potential for ecological harm, based on comparison with established international sediment quality guidelines. The Contamination factor (CF) and the geoaccumualtion index (Igeo) of As, Pb, Zn, Cu, Ni, and Cr were computed to determine the pollution status of the mangrove and foreshore sediments. The lowest effect level (LEL) and the severe effect level (SEL) esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, any potential influence in nutrient dynamics, as indicated by stable isotope tracers, is likely to extend to regional trophic levels owing to the high connectivity between mangroves and surrounding marine habitats (Kwon, ). Additionally, urban mangrove soils seem particularly prone to accumulating heavy metal and Polycyclic aromatic hydrocarbon (PAH) contaminants, often to toxic levels for some floral and faunal species (Diallo & Ishiga, ; MacFarlane, ; Ventura & da Cunha Lana, ). Although there is some field‐based evidence for the effect these contaminants have in driving the composition of benthic faunal assemblages, mostly laboratory experiments have shown direct impacts on mangrove floral physiology, indicating a need for more in situ experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, any potential influence in nutrient dynamics, as indicated by stable isotope tracers, is likely to extend to regional trophic levels owing to the high connectivity between mangroves and surrounding marine habitats (Kwon, ). Additionally, urban mangrove soils seem particularly prone to accumulating heavy metal and Polycyclic aromatic hydrocarbon (PAH) contaminants, often to toxic levels for some floral and faunal species (Diallo & Ishiga, ; MacFarlane, ; Ventura & da Cunha Lana, ). Although there is some field‐based evidence for the effect these contaminants have in driving the composition of benthic faunal assemblages, mostly laboratory experiments have shown direct impacts on mangrove floral physiology, indicating a need for more in situ experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Municipal sewage has also been a frequent topic of urban mangrove studies, many of which have reported anthropogenic nitrogen enrichment in these systems, as evident in higher foliar and detrital δ 15 N isotopes (Cifuentes et al, ; Dehairs et al, ; Fry & Cormier, ; Jones, O'Donohue, Udy, & Dennison, ; Mohamed et al, ; Wolters, Gillis, Bouma, Katwijk, & Ziegler, ) and lower foliar carbon to nitrogen ratios (C:N; Mohamed et al, ; Wolters et al, ). Many studies also report high heavy metal contamination in urban mangrove sediments, attributable not only to increased metal inputs associated with urban land use, but also to the high metal affinity of the mangrove benthos (Bayen, ; Cavalcante, Sousa, Nascimento, Silveira, & Freire, ; Defew, Mair, & Guzman, ; Diallo & Ishiga, ; Harris & Santos, ; Inglis & Kross, ; Lai et al, ; Li, Xu, Chai, & Qiu, ; Oliveira, Souza‐Santos, Silva, & Macedo, ; Pagliosa & Barbosa, ; Shriadah, ; Tam & Wong, ; Wasserman, Freitas‐Pinto, & Amouroux, ). These metals are assimilated by mangroves and partitioned throughout their biomass (MacFarlane, Koller, & Blomberg, ), with some reported influences on their physiology and morphology (Liu et al, ; MacFarlane, ; MacFarlane & Burchett, ).…”
Section: Introductionmentioning
confidence: 99%
“…These enrichments in the central zone can be attributed to Fe-rich clay deposit in the deepest part of the impoundment. Fe -oxide is considered an excellent trapper of trace metals (Diallo & Ishiga, 2016).…”
Section: 2 the Central Zonementioning
confidence: 99%